The Role of Industry in Addressing the Six Dimensions of the New Environmental Paradigm - Agustina, Nazwa Aida Dwi; Utari, Enggar; Sarifah, Sarifah; Saefulloh, Aef; Safitri, Safitri; Erfiyana, Rina (Universitas Pakuan, 2025)
Industrial development remains a major driver of economic growth while simultaneously contributing to severe environmental degradation. This study aims to examine how industrial communities perceive and respond to the six key dimensions of the New Environmental Paradigm (NEP): anti-anthropocentrism, the fragility of nature’s balance, the possibility of an ecological crisis, rejection of human exemptionalism, limits to growth, and belief in human capability through science and technology. Using a descriptive qualitative approach, data were collected through semi-structured questionnaires and interviews with 21 respondents residing near the industrial zone of Kampung Kadingding, Tambak Village, Kibin District, Serang Regency, Indonesia. The results reveal a relatively high level of ecological awareness among respondents, particularly concerning the fragility of natural balance (mean score = 69) and the risk of an ecological crisis (mean score = 64). However, lower agreement was observed in the dimensions of anti-anthropocentrism (mean score = 60) and limits to growth (mean score = 68), suggesting persistent anthropocentric and growth-oriented perspectives. These findings indicate a cognitive dissonance between environmental consciousness and economic dependency within industrial communities. The study underscores the need for integrating environmental education, policy enforcement, and corporate social responsibility programs to bridge the gap between ecological values and industrial behavior.